(untitled) (Indian Journal of Arid Horticulture, 2025)
Leucaena leucocephala is a highly drought and salinity tolerant plant species tolerating as high temperature as 48°C (Hocking, 1993). It is a species of small Mimosoid tree that is native to southern Mexico and northern Central America but now naturalized throughout the tropics. In India, it is also known as Subabul and grown for multiple uses, such as green manure, charcoal making, hedge plants besides being widely used in agro-forestry system and wind break plantation for its tremendous ability to survive amidst a wide range of environment and soil factors.Except being high in sodium and iodine content, it is a balanced livestock fodder that provides supplemental protein along with minerals in tropical areas. Its leaves have high nutritive fodder for live stock thriving in arid regions. Plant is used for soil conservation and crop intensification (Shelton and Brewbaker, 1994). It is fast growing leguminous, nitrogen fixing multipurpose plant species (Halliday and Somasegaran, 1983).